Extra‐pair copulations can insure female blue tits against male infertility. (13th June 2020) - Santema, Peter; Teltscher, Kim; Kempenaers, Bart
Abstract : Mating outside the pair‐bond occurs frequently in socially monogamous birds, but the benefits that females gain from this behaviour remain debated. One hypothesis is that females engage in extra‐pair copulations (EPCs) to ensure that their clutch is fertilised in case their own mate is infertile, but evidence for this idea is scarce. We report on a case of an infertile male blue tit that bred in three successive years with three different females. In the first year, all eggs were sired by an extra‐pair male whereas in the second year all eggs were unfertilised and contained no sperm. In the third year, the female produced two clutches that were fertilised by an extra‐pair male, but – unlike 'normal' clutches – sperm numbers on the perivitelline membrane decreased rapidly over the laying sequence. Our findings show that blue tit females mated to an infertile male can escape reproductive failure by engaging in EPCs and support previous suggestions that EPCs in blue tits cease after the onset of egg laying.